01. Serum Bactericidal Activity Against Circulating and Reference Strains of Meningococcal Serogroup B in the United States: A Review of Meningococcal Serogroup B (MenB) Vaccines in Adolescents and Young Adults. (4th December 2021) - Coyne-Beasley, Tamera; Bocchini, Joseph; Cane, Alejandro; Burman, Cindy; Tort, Maria J; Presa, Jessica
Abstract: Background: US adolescents and young adults are at particular risk of invasive meningococcal disease (IMD). In 2018, menincococcal serogroup B was responsible for 36% of IMD cases in the US overall and for 66% of cases in adolescents and young adults. This age group is at high risk of IMD during outbreaks, which result in significant response-related costs. MenB vaccine efficacy against IMD relies on its ability to provide broad protection against diverse disease-causing strains. MenB-FHbp (Trumenba) and MenB-4C (Bexsero) are MenB vaccines licensed in the US as 2-dose series with an interval of 6 mo or 1 mo, respectively, recommended in healthy adolescents and young adults. We review available data on vaccine coverage of serogroup B strains. Methods: A literature review identified relevant information from peer-reviewed publications, congress presentations, and ClinicalTrials.gov. Previously presented but unpublished data from phase 2/3 studies were included. Results: After 2 MenB-FHbp doses, percentages of adolescents and young adults achieving serum bactericidal activity assay using human complement (hSBA) titers ≥1:8 were 79%–99% for 4 heterologous representative test strains and 71%–97% for 10 additional strains, confirming cross-protection against a diverse strain panel (Figure 1 ; unpublished data). These 14 heterologous strains collectively represent 80% of disease-causing strains in the US and Europe. In a published study with limited sample size, 44%–78% of subjects had hSBA titers ≥1:8 against strains from 4 US college outbreaks after 2 MenB-FHbp doses. After 2 MenB-4C doses, percentages of 10–25-year-olds achieving hSBA titers ≥1:5 against 3 reference strains homologous to the vaccine antigen were 82%–93% (published data); 15%–100% of adolescents achieved hSBA titers ≥1:4 against a panel of 14 strains (unpublished data). Of college students who received 2 MenB-4C doses, 53%–93% achieved hSBA titers ≥1:4 against 5 US outbreak strains (4/5 strains had antigenic similarity to MenB-4C; published data). Conclusion: MenB-FHbp and MenB-4C protect against various serogroup B strains. As for the breadth of coverage provided by these vaccines, available data show that MenB-FHbp elicits robust immune responses to a wide variety of disease-causing strains prevalent in the US (Figure 2 ). Disclosures: Tamera Coyne-Beasley, MD, MPH, Pfizer Inc and GlaxoSmithKline (Advisor or Review Panel member) Joseph Bocchini, MD, Pfizer Inc and Dynavax (Advisor or Review Panel member) Alejandro Cane, M.D., Pfizer Inc (Employee, Shareholder) Cindy Burman, PharmD, Pfizer Inc (Employee, Shareholder) Maria J. Tort, PhD, Pfizer Inc (Employee, Shareholder) Jessica Presa, MD, Pfizer Inc (Employee, Shareholder)